PENGEMBANGAN DESA WISATA DALAM PERSPEKTIF COMMUNITY BASED TOURISM (CBT) - I Gusti Ayu Mitha Purnama Sari (Faculty of Social and Political Science, 2020)
This study aims to describe the tourism village development in Community-Based Tourism in Café Sawah located in Pujon Kidul Village Malang. It uses qualitative descriptive method with the theoretical approach of CBT (Community-Based Tourism) from Suansri (2003) consisting of economic, social, cultural, environmental and political indicators. The output of this study reveals that the tourism village development at the CBT (Community-Based Tourism) from the economic point of view opens job opportunities for the jobless people. From the social point of view, it activates the community participation in a tourism aware group, whereas from cultural view point, the village communities have not yet been involved through the traditional dances in order to become the attraction in Café Sawah tourism object. From the environmental point of view, the people actively get involved in ‘gotong royong’ – working together hand-in-hand for a certain purpose. In term of political aspect, the people protect and embrace others for development of Café Sawah.